Benchmarking the permanent magnet electrical variable transmission against the half toroidal continuously variable transmission. (July 2017) - Verbelen, Florian; Druant, Joachim; Derammelaere, Stijn; Vansompel, Hendrik; De Belie, Frederik; Stockman, Kurt; Sergeant, Peter
Highlights: A method to benchmark a permanent magnet Electrical Variable Transmission against a half toroidal continuously variable transmission is proposed. The efficiency of both technologies is discussed in the complete operating range during steady state. The CVT is in favor for high input torques and that the EVT is dominant for high input speeds. Abstract: In most applications where a variable transmission is required, either an EVT or a CVT would be viable options. In order to obtain a justified decision between both variable transmissions, the operating range and efficiency should be known better. To be able to pinpoint the pros and cons based on efficiency and operating range, a detailed comparison is necessary. However, to the knowledge of the authors there is no such study reported in literature so far. In this paper a permanent magnet Electrical Variable Transmission (EVT) is benchmarked against a half toroidal Continuously Variable Transmission (CVT) and this during steady state conditions. This paper provides the constraints for the comparison and results based on detailed models of both technologies. Two comparative studies are carried out: on one hand a study based on equal maximum output torque and on the other hand a study based on equal rated power. The outcome of the study shows that the CVT is in favor for high input torques and that the EVT is dominant for high input speeds.